High temperature electronics - A European prespective - Johnston, C (2008)
High temperature electronics (HTE) has been a European research theme since HITEN, the High Temperature Electronics Network of Excellence was established in 1990. This paper reviews current pan European projects in HTE and illustrates the growing number of national programmes and commercial imperatives driving this increased activity. A number of HTE projects will be reviewed and the commercialisation strategy with respect to Europe discussed.